Detection of Telomerase Activity and the Expression of Telomerase Subunits in the Patients with Acute Myelogenous Leukaemia - 李一荣 吴健民 王琳 陈凤花 胡丽华 (Current medical science, 2004)
Telomerase activity and the expression of telomerase subunits (for example, telomerase reverse transcriptase and telomerase associated protein 1 and telomerase RNA component) of peripheral white blood cells were detected in the patients with acute myelogenous leukaemia (AML) and the correlation between telomerase activity and the expression of telomerase subunits was observed. In 94 peripheral white blood cells from 18 healthy volunteers and 76 patients with AML,including 31 AML at initial presentation, 24 at relapse and 21 at complete remission, the telomerase activity and telomerase subunits mRNA or RNA were detected by PCR-ELISA and RT-PCR respectively. The results showed that the positive rate of telomerase from patients with AML at initial presentation, at relapse and at complete remission was 74.1%, 79.2% and 4.8% respectively.The positive rate of telomerase reverse transcriptase mRNA from healthy volunteers, AML at initial presentation, AML at relapse and AML at complete remission was 5.6%, 80.6%, 83.3%and 9.5% respectively. The positive rate of telomerase associated protein 1 mRNA and telomerase RNA component in all samples were 100%. It was suggested that the up-regulation of telomerase activity and the expression of telomerase reverse transcriptase is correlated closely with the occurrence and relapse of AML, so telomerase activity and the expression of telomerase reverse transcriptase may be used to estimate the curative effect and predict relapse of AML. Moreover, the upregulation of telomerase activity is correlated with the expression of telomerase reverse transcriptase significantly.